Formulating a Horseradish Extract in Phospholipid Vesicles to Target the Skin - Maria De Luca; Luca Casula; Carlo Ignazio Giovanni Tuberoso; Ramon Pons; Maria del Carmen Morán; María Teresa García; Giuseppe Martelli; Antonio Vassallo; Carla Caddeo (Pharmaceutics)
Background/Objectives: Horseradish (Armoracia rusticana L.) roots—largely used in traditional medicine for their multiple therapeutic effects—are a rich source of health-promoting phytochemicals. However, their efficacy can be compromised by low chemical stability and poor bioavailability. Incorporation into phospholipid vesicles is often proposed to tackle this problem. Methods: In this study, a hydroalcoholic extract was produced from horseradish roots. The extract was characterized by UPLC-MS and HPLC-PDA and formulated in conventional liposomes and Penetration Enhancer-containing Vesicles (PEVs) for skin application. Results: The obtained nanovesicles were small in size (<100 nm), negatively charged, uni/bilamellar, and with high values of entrapment efficiency (>85%) for the flavonoids identified in the extract. Both the free and the nanoformulated extract showed optimal biocompatibility, measured as the absence of hemolysis of erythrocytes and absence of cytotoxicity in skin cell lines. Furthermore, the nanoformulations displayed antioxidant activity in vitro. Conclusions: The proposed nananoformulations could be exploited to counteract oxidative stress involved in the pathogenesis and progression of numerous skin disorders.